(untitled) (GEOMATE Journal, 2025)
This work introduces a novel teaching model that pairs graduate students with experts and engineers from both academia and the geotechnical industry. It was proposed to hold regular gatherings to talk about and share ideas regarding failures, malfunctions, and performance of structures found on difficult soils. Issues related to failure in the construction industry are frequently reported in practice. A three-to-five-hour sessions covering a specific problem or case study failures were suggested as a contact period to expose graduate students to the prevalent difficulties identified in geotechnical practice. A research unit created a geotechnical evening series, which is held once or twice a year. It is anticipated that exposure to real-world geotechnical issues and failures will heighten consciousness and instruct future engineers on how to prevent or address typical malfunctions and failures. Targeted objectives include the ability to predict failures related to materials and structures, the ability to evaluate the level of risk based on available data, and the development of good communication skills. A learning model is suggested to be developed as an educational civil engineering course based on typical gatherings. Direct and indirect assessment methods are proposed as guidance. Participant satisfaction score levels were reported as good to excellent.